THE IMPACT OF REGIONAL TRADE AGREEMENTS TO THE COMMODITY TRADE FLOWS (CASE STUDY: INTERNATIONAL PALM OIL TRADE) - Riska Pujiati; Muhammad Firdaus; Andriyono Kilat Adhi; Bernhard Brummer (Forum Agribisnis, 2014)
Indonesia and Malaysia are the major exporters of palm oil in South East Asia. South East Asia Regional Trade Agreement can affect worldwide trade flow of palm oil. The objective of this study is to examine the effect of the Regional Trade Agreement on the trade flows of Indonesian and Malaysian palm oil. The effect is analyzed with gravity model.  The result shows positive dynamic effect of Free Trade Agreement to palm oil trade flow. Regional Trade Agreement has higher impact to Malaysia than Indonesia due to dissimilar government policies.